Adoption of a town-wide forensic structural investigation procedure for typhoon effects a case study of Palo, Leyte, Philippines - Valdez, Justin Joseph P.; Pacheco, Benito M.; Suiza, Raniel M.; Aquino, Diocel Harold M. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
The typhoon is one of the most common disasters that occurs in the Philippines. Typhoon Haiyan (local name: Yolanda), the strongest recorded typhoon in recorded history, made landfall in the Philippines last 8 November 2014. It is difficult to determine the extent of damage of the typhoon, or in other words, if the structures in a town were damage by severe wind alone or the combination of severe wind and storm surge. Such is the case of the municipality of Palo, province of Leyte. Since there is no comprehensive town-wide structural investigation exists in the country, a forensic structural investigation was adopted to incorporate the are-wide study and utilization of mass media. Systematic gathering of data from a site survey and from mass media was demonstrated using a web crawl, with validation methods. A total of 41 structures were documented in the dataset. An initial hypothesis that the Pan-Philippine Highway served as a barrier to the storm surge was established, grouping the structures into the severe wind load only (west) and combined severe wind and storm surge load (east) groups. It was determined that the significant damages on doors and exterior walls were distinct to storm surge loading, and the boundary of storm surge inundation was identified. The results supported the initial hypothesis, but documentation of more structures was recommended. Critical analyses on the materials used in roof covering windows and exterior walls, location of critical fucilities, and investigation of specific structures were further emphasized.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Forensic engineering; Structural failures -- Investigation; Palo (Leyte, Philippines).